2011
DOI: 10.4103/0019-5545.91904
|View full text |Cite
|
Sign up to set email alerts
|

Are anxiety disorders associated with a more severe form of bipolar disorder in adolescents?

Abstract: Background:Anxiety disorders are common among children and adolescents with bipolar disorder. Among adults, anxiety disorder comorbidity is associated with a more severe form of bipolar disorder and a poorer outcome. There is limited data on the effect of comorbid anxiety disorder on bipolar disorder among children and adolescents.Aim:To study the prevalence of anxiety disorders among adolescents with remitted bipolar disorder and examine their association with the course and severity of illness, global functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…Sixteen of the included studies reported the prevalence of ADHD in patients with PBD 14,15,27–40 . The studies showed that comorbid ADHD occurred in 0%–87.1% (weighted mean prevalence = 59.5%) of patients with PBD.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sixteen of the included studies reported the prevalence of ADHD in patients with PBD 14,15,27–40 . The studies showed that comorbid ADHD occurred in 0%–87.1% (weighted mean prevalence = 59.5%) of patients with PBD.…”
Section: Resultsmentioning
confidence: 99%
“…The studies showed that comorbid ADHD occurred in 0%–87.1% (weighted mean prevalence = 59.5%) of patients with PBD. Current comorbid ADHD occurred in 15%–70% (weighted mean prevalence = 51.4%) of patients in remission 15,33 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations